Freedom of Parties to Choose the Title of Litigation: To Be True or Not True in Accepting the Litigation of Homologation - Ali Shamsi; Hassan Mohseni (پژوهشهای حقوقی)
Right to action as a natural right recognized in Constitution an International Pacts. Except some rare cases, everybody is free to act with this right. The conflict is a pre se requisite of litigation but we see some cases by the subject of homologation a contract which has not yet a conflict and courts have not a similar jurisprudence in cases. Although courts can, qualification or requalification the title of litigation but the manner is civil cases is different and the courts can see the cases, which permitted by laws and regulations exceptionally. We think that a litigant has profit to litigate and so we are trying to critic the case law and courts can, qualification or requalification the title of litigation but the manner is civil cases is different and the courts can see the cases, which permitted by laws and regulations exceptionally. So as a result, every conflict by a legal consequence will be accepted as litigation.